Recent Progress in Equilibrium Acidity Studies of Organocatalysts - Li, Zhen; Li, Xin; Cheng, Jin-Pei (Synlett, 2019)
This account summarizes our recent work on the pKa scales of some frequently used organocatalysts, especially those of hydrogen-bond-donor catalysts and stronger Brønsted acid catalysts. Most of these pKa values were obtained by the Bordwell overlapping indicator method, which is known to provide high accuracy. Linear free-energy relationships associated with pKa values are discussed in relation to understanding of reaction mechanisms.1 Introduction2 Single Hydrogen-Bonding Donors2.1 Proline-Type Organocatalysts2.2 Cinchona Alkaloids Bearing a Hydrogen-Bonding Donor in the 6′-Position3 Double-Hydrogen-Bonding Donors3.1 Thioureas3.2 Squaramides3.3 BINOLs4 Stronger Brønsted Acids5 N-Heterocyclic Carbenes6 Summary and Outlook
Keywords: acidity; organocatalysis; hydrogen-bonding donor catalysis; Brønsted acid catalysis; N-heterocyclic carbenes